Forest-Water Interactions Under Global Change - Jones, J.A.; Wei, X.; Archer, E.; Bishop, K.; Blanco, J.A.; Ellison, D.; Gush, M.B.; McNulty, S.G.; Noordwijk, M. van; Creed, I.F. (Springer, 2020)
This chapter reviews how global change affects forest-water interactions and water availability to ecosystems and people and synthesises current understanding of the implications of present and anticipated changes to forests and tree cover for local and global hydrology. Forest cover has declined in the past half-century, despite an increase in plantation forestry. Natural and human disturbances affect forest components (e.g. canopy and leaf area, litter and soil surface, rooting depth, and soil porosity) that in turn affect hydrological processes (e.g. interception, evapotranspiration, infiltration, soil moisture storage, and percolation). Many of these changes result from several influential natural disturbance processes including insects and pathogens, wildfire, ice storms, and windthrow, and human disturbances including establishment and harvest of forests, plantations, agroforestry areas, and urban/peri-urban forests. However, each disturbance process affects different components of the forest, producing distinctive hydrologic effects. Climate change will directly alter forest hydrological processes, and social and economic factors will directly alter forest management, via intensive plantations, deforestation, forest degradation, selective logging, loss of riparian forest, and loss of urban trees, and changes in disturbance regimes. Despite extensive knowledge of forest hydrology, forest changes and their effects on hydrology are poorly documented in many areas of the world, and novel combinations of processes and contexts may produce surprising outcomes. Thus, there is a clear need for more geographically extensive and long-term place-based studies of forest and water. In summary, future climate and social changes will alter forests and water, requiring continued research and collaboration with forest managers and forest owners both for improved resilience to such changes, and to better realize multiple benefits.